2016
DOI: 10.1016/j.cyto.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targets in fibrotic pathways

Abstract: The pathogenetic heterogeneity of pulmonary fibrosis yields both challenges and opportunities for therapy. Its complexity implicates a variety of cellular processes, signaling pathways, and genetics as drivers of disease. TGF-β stimulation is one avenue, and is central to pro-fibrotic protein expression, leading to decreased pulmonary function. Here we report our recent findings, introducing the E3 ligase Fibrosis Inducing E3 Ligase 1 (FIEL1) as an important regulator of TGF-β signaling through the selective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…It is known that TGF-b1 increases the generation of free radicals such as reactive oxygen species and reactive nitrogen species in lung fibroblasts [41]. It has been reported that during BLM injury, TGF-b1 mRNA expression increases predominantly in various cells such as alveolar macrophages, fibroblasts, endothelial cells and mesothelial cells [42,43]. In accordance with these reports, the result of our study shows a pronounced expression of TGF-b1 in lung tissue sections of rats induced with BLM.…”
Section: Discussionsupporting
confidence: 91%
“…It is known that TGF-b1 increases the generation of free radicals such as reactive oxygen species and reactive nitrogen species in lung fibroblasts [41]. It has been reported that during BLM injury, TGF-b1 mRNA expression increases predominantly in various cells such as alveolar macrophages, fibroblasts, endothelial cells and mesothelial cells [42,43]. In accordance with these reports, the result of our study shows a pronounced expression of TGF-b1 in lung tissue sections of rats induced with BLM.…”
Section: Discussionsupporting
confidence: 91%
“…Analyses have indicated that the DCGs such as TGF-β, SMAD, MMP-2 and MMP-9 are mapped with different pathways related to stimulation, signaling cascades and pro-fibrotic protein expression. The role of these pathways was reported in early and late-onset ILDs pathogenesis ( 24 , 26 ). Pathways analyses of the DCGs have also suggested their significant involvement in the immune system (134 DCGs), innate immune system (91 DCGs), signal transduction (67 DCGs) and cytokine signaling (59 DCGs).…”
Section: Resultsmentioning
confidence: 98%
“…Outcomes of biological processes have shown that the maximum number of DCGs such as IL-4, IL-7, IL-8, IL-10 and CCL-ligands are mapped with defense response (90), response to external stimulus (84) and immune system process (74) ( Supplementary Figure S1C ). Identified cellular components for the majority of DCGs are extracellular region part (148), extracellular space (112) and few are from the intrinsic component of the membrane ( 24 ) ( Supplementary Figure S1B ). Results of molecular function have shown that the most of DCGs are mapped with cytokine activity ( 32 ), small molecule binding ( 12 ), chemokine receptor binding ( 11 ) and nucleoside binding ( 7 ) ( Supplementary Figure S1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since E3 ligases responsible for targeting most proteins have not been identified the first step will be to catalog the E3 ligases responsible for controlling protein expression in relevant cell populations in the lung. Once achieved, the next step will be to develop small molecules capable of augmenting or inhibiting the activity of specific E3 ligases, like has recently been done for specific E3 ligases in the cancer field [83, 84, 85]. Alternatively, one could also develop small molecules that bind preferentially to specific substrates or to their ancillary proteins rather than to an E3 ligase.…”
Section: Proteasome Dysfunction In Ipfmentioning
confidence: 99%